The 1980s African Social History and E. P. Thompson's Works: the case of the wits history workshop - Macedo, Francisco Barbosa (2021)
The article analyses the 1980s South African social history, focusing on the Wits History Workshop's (WHW) production, institution largely recognized as the main diffusion and production center of the new historiographical approach in the country. Besides pointing out conditions of emergence, crucial themes, and recurrent analytical axis of the 1980s South African social history, the article also highlights the centrality of E. P. Thompson's works in this production, especially in that one related to the WHW.